The Power of Proof In Victims of Sexsual Abuse - Maswandi, Maswandi; Jamillah, Jamillah; Sitompul, Ariman (Faculty of Law, Universitas Pattimura, 2022)
Introduction: Enforcement and legal protection for sexual assault cases has focused on protecting the victims of sexual assault law which consists of physical or psychological violence, retaliation, humiliation, and mistreatment of people who support victims of violence against women in particular. Where the focus of this tuilsan mebahas about the legal protection of victims of sexual violence in Indonesian criminal law and how the penultimate case of sexual violence.Purposes of the Research: The purpose of this study is to explain the concept Absentia trial by applying the return of State.Methods of the Research: The research method used is normative legal research with a statute legal approach and a conceptual approach.Results of the Research: Sexual violence itself becomes an urgency, given the rise of cases of sexual violence in Indonesia. By creating laws that protect victims of sexual violence, the resolution of sexual violence cases and the protection of victims of sexual violence cases can be executed well. So that the law in Indonesia can be implemented in accordance with its purpose, which is to protect all Indonesian people from crime cases.